2018
DOI: 10.1186/s12893-018-0427-y
|View full text |Cite
|
Sign up to set email alerts
|

Crystalloid resuscitation in trauma patients: deleterious effect of 5L or more in the first 24h

Abstract: BackgroundOver-aggressive intravenous fluid therapy with crystalloids has adverse effects in trauma patients. We assessed the role of large-volume (≥5l) administration of crystalloids within 24h of injury as an independent risk-factor for mortality, in-hospital complications, and prolonged mechanical ventilation.MethodsA retrospective cohort analysis of adult trauma patients admitted to a level 1-trauma center between December 2011 and December 2012. Patient demographics, clinical and laboratory values, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…In this study, up to 10 L of crystalloids < 24 hours did not seem to increase MODS and mortality whereas 5 L crystalloids < 24 hours appeared to be a cut-off point for a doubling in infectious complications and ARDS, although the incidence of ARDS was likely too small to draw any conclusions. Jones et al 33 previously also demonstrated that >5 L of crystalloids < 24 hours was associated with adverse outcomes, although results are not fully comparable since patients in their study were less severely injured.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In this study, up to 10 L of crystalloids < 24 hours did not seem to increase MODS and mortality whereas 5 L crystalloids < 24 hours appeared to be a cut-off point for a doubling in infectious complications and ARDS, although the incidence of ARDS was likely too small to draw any conclusions. Jones et al 33 previously also demonstrated that >5 L of crystalloids < 24 hours was associated with adverse outcomes, although results are not fully comparable since patients in their study were less severely injured.…”
Section: Discussionmentioning
confidence: 81%
“…In total, 367 patients (70% male) with a median age of 46 (28-61) years who were admitted to ICU and survived 48 hours were included. Ninety-six percent of injuries were caused by a blunt mechanism and median ISS was 29 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) with most severe injuries located in the brain (AIS head 3 (1-3)) and chest (AIS chest 3 (2-4)). Eighty-six patients (23%) underwent an urgent laparotomy (table 1).…”
Section: Results Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the trauma community has moved away from standardized crystalloid administration, as crystalloids worsen coagulopathy and increase mortality. 7,8 A balanced transfusion, with near-equal amounts of red blood cells, plasma, and platelets, should be used whenever possible to reduce the risk of coagulopathy. A 1:1:1 transfusion approach of 6 units of red blood cells, 6 units of fresh frozen plasma, and one 6-pack of platelets has been shown to decrease the risk of death from bleeding in the first 24 hours after trauma.…”
Section: Circulationmentioning
confidence: 99%